Corporate social responsibility under the UK Corporate Governance system - Saidov Ibrokhim Anvarovich (Genius Journals, 2023)
This essay explores how corporate social responsibility has a great impact to society and which measures have been taken by governments to protect social and environmental issues. Firstly, it shows the main problems of legislation to support CSR in the light of UK Corporate Governance Code. Then it compares merits and drawbacks of hard and soft law in order to identify the most way to support CSR. At the end it gives some recommendations to improve the interconnected frameworks
Keywords: Corporate social responsibility; Corporate Governance; sustainability